Software Configuration Management. - Estublier, Jacky (Computer (00189162), 2008)
The article discusses as study which investigated the impact of the software configuration management (SCM) discipline on the software industry at large. The team assembled for the study was comprised of primary architects from two major SCM system vendors, two academic researchers and three contributors with both industrial and academic experience. It was demonstrated by the study that accurately pinpointing the origins of most ideas is difficult. It was found that the international academic community serves an important role by providing a forum.